2020
DOI: 10.1371/journal.ppat.1008619
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic rotation of the protruding domain enhances the infectivity of norovirus

Abstract: Norovirus is the major cause of epidemic nonbacterial gastroenteritis worldwide. Lack of structural information on infection and replication mechanisms hampers the development of effective vaccines and remedies. Here, using cryo-electron microscopy, we show that the capsid structure of murine noroviruses changes in response to aqueous conditions. By twisting the flexible hinge connecting two domains, the protruding (P) domain reversibly rises off the shell (S) domain in solutions of higher pH, but rests on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 56 publications
4
35
1
Order By: Relevance
“…A recent study 34 has reported that GII.3 VLPs exhibit two different conformations of the P-domain dimer in which one conformation of the P-domain is rotated by ~70° and elevated above the shell domain compared to the other conformation. A similar rotated and elevated state also is observed in the case of murine norovirus capsid structure 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 34 has reported that GII.3 VLPs exhibit two different conformations of the P-domain dimer in which one conformation of the P-domain is rotated by ~70° and elevated above the shell domain compared to the other conformation. A similar rotated and elevated state also is observed in the case of murine norovirus capsid structure 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This observation is surprising in the context of the previous literature, which would have better supported a role for specific P2 amino acids in mediating altered tropism and increased virulence. However, recent reports have suggested that norovirus capsid structures may be highly dynamic and that the P1 domain may govern this flexibility by regulating interactions with the shell domain [58][59][60][61][62]. We hypothesize that residue 514 may be involved in this flexibility, as several amino acids with which it is predicted to interact make up a portion of this flexible linker, in the capsids of both MNoV S7 (which possesses F514) and CW3 (which possesses I514) (S9 Fig) . F/I514 may influence this linker to adopt either the "expanded" or "closed" conformation, changing the capsid structure and altering its ability to interact with receptors and/ or the immune system.…”
Section: Plos Pathogensmentioning
confidence: 90%
“…The P domain has recently been shown to support two conformations (Smith & Smith, 2019), namely the rising conformation as evidenced in MNV (Katpally et al, 2008), HuNoV GII.10 (Hansman et al, 2012 and GII.4 (Devant et al, 2019), where the P domain rises from the S domain surface, and the resting conformation as represented by GI.1 (Prasad et al, 1999) and GII.2 viruses (Jung et al, 2019), where the P domain rests upon the S domain. Moreover, dynamic conformational changes have been reported for MNV and HuNoV GII.3; whilst the MNV conformational changes have been reported in response to aqueous conditions (the P domain rises from the S domain surface in solutions with higher pH and rests in solutions with lower pH (Song et al, 2020)), the mechanism is yet unclear for GII.3 viruses. The accessibility of S domain epitopes may be inferred from the dynamic rotation of the P domain.…”
Section: Discussionmentioning
confidence: 99%